ChemInform Abstract: Electronic Structure of Tantalum Oxynitride Perovskite Photocatalysts. Issue 43 (7th October 2013) - Balaz, Snjezana; Porter, Spencer H.; Woodward, Patrick M.; Brillson, Leonard J.
Abstract The absolute conduction and valence band energy levels of MTaO2N (M: Ca, Sr, Ba) and PrTaON2, which are promising candidates for photocatalytic splitting of water under visible light irradiation, are determined by a combination of XPS, Kelvin probe force microscopy, UV/VIS spectroscopy, and depth‐resolved cathodoluminescence spectroscopy.